Survei Pembinaan Prestasi Bulutangkis di PB. Exotic Kecamatan Simo Kabupaten Boyolali - Budiharjo, Satrio; Raharjo, Hermawan Pamot (Universitas Negeri Semarang, 2023)
The problem in this study is how the achievement coaching in the PB. Exotic Badminton Club, Simo District, Boyolali Regency, which includes athlete coaching, achievement organizations, facilities and infrastructure. The purpose of this study was to determine the process of the athlete coaching in PB. Exotic Badminton Club, Simo District, Boyolali Regency. This study uses a qualitative approach with the research location in the PB. Exotic Badminton Club, Simo District, Boyolali Regency. The sources of research data is (1) Person, namely: Owners, Managers, Trainers, and Athletes, (2) Place, namely the badminton training field or places. The collecting data used in study was interview, observation, and documentation methods. The data analysis used descriptive analysis. The results of this study are as follow: (1) Athlete coaching conducted in PB. Exotic, Simo District, Boyolali Regency, is quite good and directed, (2) Organizational conditions carried out by well-coordinated, familial, and open-minded administrators are shown by good administrative management with funding assisted by cross subsidies to help athletes but needs to be improved, (3) The achievement achieved are very good at the Boyolali Regency level, (4) Facilities and infrastructure are quite adequate even though they are still borrowing from SMA Negeri 1 Simo. The conclusions from the results of the study are: (1) Achievement Development is carried out according to the program that has been made by the coach and agreed upon by the athlete in cooperation with the parents (2) The organization is quite good as shown by good administrative management by club administrators with funding assisted by parents through cross subsidies for helping underprivileged athletes, (3) very encouraging achievement by winning a prestigious match event in Boyolali Regency, (4) facilities and infrastructure are adequate and in accordance with existing standards as training support facilities even though they are borrowed at SMA Negeri 1 Simo.